Race, Music, And Meaningful Approach To Teaching Historical Methods - Hughes, Richard (Teaching History: A Journal of Methods, 2010)
Oliver Sacks, a neurosurgeon in New York City and the well-known author of Awakenings, recently described the case of a forty-two year old man named Tony Cicoria who was struck by lightning. After almost dying at a nearby hospital, Cicoria appeared to recover fully within weeks, only to discover that, for the first time in his life, he had what Sacks referred to as an "insatiable desire to listen to piano music." The individual had no formal musical training and yet within months he began teaching himself how to play the piano and eventually began composing complex, original works. In his book Musicophelia , Sacks describes other patients, many quite elderly, who discovered that music long forgotten from childhood had the ability to induce seizures. Such cases suggested to Sacks the powerful, in his words, "engraving of music on the brain." The man struck by lightning was a dramatic example of how humans are inescapably a "musical species."1 While Sacks explored the "extraordinary tenacity of music memory" or the role of music in shaping the cognitive map of individuals, my interest as a historian lies in the power of music in illuminating what Abraham Lincoln referred to as our "mystic chords of memory." Speaking at his first Inaugural Address in March 1861, Lincoln used the metaphor of music to remind an increasingly divided nation that the "chorus of the Union," his term for collective memory, lay embedded not in Americans’ neurology but rather in "every living heart." As a result, when I agreed to teach a required historical methods course with a rather dry catalog description-"An introduction to the discipline, including study of research and writing techniques, historical methods, and the nature and varieties of history"- I chose to use music as the focus. I entitled my section "Doing History: Race and American Music" and aimed to ground the course on methodology in what I hoped would be the meaningful historical context of African-American history and music.2